The Physical and Social Components of Hairdressing Establishments that Affect the Preferences of selected Filipino Male Customers in Metropolitan Manila and Rizal - Soriano Wesley Ronzon E.; Florendo, Raquel Baltazar (Quezon City: College of Home Economics, University of the Philippines Diliman, 2014.)
ABSTRACT The study determined the physical and social components of hairdressing establishments and assessed how these components affect the preferences of selected Filipino male customers. Quantitative and qualitative research through an explanatory approach with the help of triangulation method was used throughout the course of the study. Survey questionnaires and in-depth interviews were completed by 31 respondents and 12 informants consisted of Filipino males with the age range of 22-62 years old. The results have shown that interior lighting was highly considered among male customers because of its monitoring and security purposes while sound and odor, which were believed to be accustomed in hairdressing establishments, were the least considered components. Other physical components were considered as deal breakers in males? preferences: the comfort a space can give while waiting and the color scheme of the interior which also establishes the men and women culture of barbershops and salons, respectively. Moreover, much of the preferences of males were affected by the social components of hairdressing establishments. The identity of the customer and service provider plays a major role in their interaction, relationship and communication. Customer?s attitude on certain issues and the professionalism of service providers affect males? preferences on hairdressing establishments. The root cause of alienating male customers in the culture of beauty may be solved through design appropriation of physical components and the awareness of the perceptions of male customers in the social aspect of hairdressing establishments.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Beauty shops -- Decoration -- Philippines